Assessing psychological health and reproductive function: Depression, anxiety, and stress in infertile men compared to controls: A case-control study - Seyedeh Narjes Roudbaraki; Maryam Ramezani; Bita Saifi; Mostafa Salimi; Massood Issapour Cheshani (International Journal of Reproductive BioMedicine)
Background: With the increasing prevalence of infertility and its links to depression, anxiety, and stress, it is essential to compare these mental health levels between infertile men and a control group. Objective: This study aimed to compare depression, anxiety, and stress among infertile and fertile men. Also, assessing demographic factors affecting these challenges among both groups. Materials and Methods: This case-control study was conducted on 120 men at Milad Infertility Research Center, Mashhad, Iran from January 2023 to February 2023. Participants were divided into 2 groups: 60 infertile men and 60 healthy men who did not have fertility problems. Demographic information such as age, education, occupation, duration of the marriage, and duration of infertility was collected from their medical records, and they also completed the depression, anxiety, and stress scale 21 questionnaire through a telephonic interview. Finally, the findings were statistically analyzed. Results: Severe and very severe depression, anxiety, and stress were observed in 65%, 60%, and 43.4% of infertile men and 16.7%, 23.3%, and 11.7% of fertile men, respectively. Which was significantly more than the fertile group, and there was a significant relationship between depression (p ≤ 0.001), anxiety (p = 0.001), stress (p ≤ 0.001), and infertility. Also, a significant relationship was observed between the duration of infertility and depression (p = 0.031).